Neo-Brandeisian Antitrust: Repeating History's Mistakes - Timothy J. Muris (American Enterprise Institute (AEI), 2023)
President Biden rejects the economics-driven antitrust policies of the past 40 years. Flanked by his White House competition adviser and his new FTC Chair in July 2021, he asserted that the "experiment failed" and promised to return to earlier antitrust traditions. This report shows those traditions were abandoned for good reason: they harmed consumers. Two such traditions are discussed in particular detail. One involves the Robinson Patman Act of 1936, which the FTC promises to reinvigorate. The second involves what FTC Chair Khan calls the "controlling precedents" of old Supreme Court merger decisions, especially from the Warren Court. Those decisions stand in sharp contrast to the modern economic standards used to evaluate mergers, as exemplified in court decisions and in the Obama administration's 2010 guidelines President Biden blamed the alleged failure on Robert Bork and the Chicago school. Blaming, or crediting, Chicago for the 40 years is inaccurate. In fact, modern antitrust analysis was much richer than any school, including Harvard professors and judges, especially Philip Areeda and Stephen Breyer, both of whom have had profound impacts. The true "failed experiment" was populist antitrust and its policies that the new enforcers praise.
Keywords: 330